Nova técnica para obtenção de fraturas com altíssima condutividade em poços de petróleo - Santos, José Altamiro Carrilho Mota dos (2010)
Increase hydrocarbons production is the main goal of the oilwell industry worldwide. Hydraulic fracturing is often applied to achieve this goal due to a combination of attractive aspects including easiness and low operational costs associated with fast and highly economical response. Conventional fracturing usually involves high-flowing high-pressure pumping of a viscous fluid responsible for opening the fracture in the hydrocarbon producing rock. The thickness of the fracture should be enough to assure the penetration of the particles of a solid proppant into the rock. The proppant is driven into the target formation by a carrier fluid. After pumping, all fluids are filtered through the faces of the fracture and penetrate the rock. The proppant remains in the fracture holding it open and assuring high hydraulic conductivity. The present study proposes a different approach for hydraulic fracturing. Fractures with infinity conductivity are formed and used to further improve the production of highly permeable formations as well as to produce long fractures in naturally fractured formations. Naturally open fractures with infinite conductivity are usually encountered. They can be observed in rock outcrops and core plugs, or noticed by the total loss of circulation during drilling (even with low density fluids), image profiles, pumping tests (Mini-Frac and Mini Fall Off), and injection tests below fracturing pressure, whose flow is higher than expected for radial Darcian ones. Naturally occurring fractures are kept open by randomly shaped and placed supporting points, able to hold the faces of the fracture separate even under typical closing pressures. The approach presented herein generates infinite conductivity canal held open by artificially created parallel supporting areas positioned both horizontally and vertically. The size of these areas is designed to hold the permeable zones open supported by the impermeable areas. The England & Green equation was used to theoretically prove that the fracture can be held open by such artificially created set of horizontal parallel supporting areas. To assess the benefits of fractures characterized by infinite conductivity, an overall comparison with finite conductivity fractures was carried out using a series of parameters including fracture pressure loss and dimensionless conductivity as a function of flow production, FOI folds of increase, flow production and cumulative production as a function of time, and finally plots of net present value and productivity index